Current trends in the physics of nanoscale friction. Issue 3 (4th May 2017) - Manini, N.; Mistura, G.; Paolicelli, G.; Tosatti, E.; Vanossi, A.
Abstract: Tribology, which studies surfaces in contact and relative motion, includes friction, wear, and lubrication, straddling across different fields: mechanical engineering, materials science, chemistry, nanoscience, and physics. This short review restricts to the last two disciplines, with a qualitative survey of a small number of recent progress areas in the physics of nanofriction. Graphical Abstract: